The Effect Of Digital Leadership On Work Productivity Based On Employee Motivation And Engagement At Maison Aurelia Sanur Hotel - Risa Pratini; Ni Made Yudhaningsih; I Dewa Nyoman Usadha; Anak Agung Elik Astari (Cita konsultindo, 2026)
Digital transformation in the hospitality industry demands adaptive leadership capable of leveraging technology to sustain employee productivity. This study examines the influence of digital leadership on employee motivation, employee engagement, and work productivity, as well as the mediating roles of motivation and engagement in that relationship, at Maison Aurelia Sanur Hotel, Bali, Indonesia. Employing a quantitative explanatory design, data were collected via structured questionnaires administered to all 40 hotel employees through a saturated (census) sampling technique. Partial Least Squares – Structural Equation Modelling (PLS-SEM) was applied using SmartPLS 4 software to test direct and indirect hypothetical relationships. Results confirm that digital leadership positively and significantly influences employee motivation (β = 0.482, t = 2.730, p = 0.006), employee engagement (β = 0.764, t = 9.147, p = 0.000), and work productivity (β = 0.318, t = 3.458, p = 0.001). Employee motivation (β = 0.386, t = 3.988, p = 0.000) and employee engagement (β = 0.357, t = 3.294, p = 0.001) also significantly predict work productivity. Mediation testing further establishes that both variables serve as significant mediators, with indirect effects of 0.186 (through motivation, p = 0.019) and 0.272 (through engagement, p = 0.003) respectively. The model accounts for 79.5% of the variance in work productivity (R² = 0.795; Q² = 0.934). These findings underscore the strategic importance of strengthening digital leadership as a managerial approach to improving employee productivity through motivational and engagement mechanisms in the hospitality context.